Hospital Leading Improvements: Discrete Event Simulation as a Strategy to Reduce Patient Length of Stay in the Emergency Department - Triana, I Ketut Dian Lanang; Paramarta, Vip; Syahidin, Rukhiyat; Yanti, Ni Putu Emy Darma (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Emergency Department (ED) frequently encounters operational challenges such as overcrowding, prolonged waiting times, and inefficient patient flow, which negatively impact healthcare service delivery. Therefore, several efforts can be made to improve efficiency and service quality through systematic events improvement. The Discrete Event Simulation (DES) could be a promising effort to effectively alleviate the patients’ Length of Stay (LOS). This study aimed to assess the role of DES in reducing patient LOS and improving ED efficiency. A literature review was conducted by analyzing peer-reviewed articles published in the past five years from databases including Google Scholar, PubMed, and ProQuest, using specific keywords related to DES and ED performance. The selected studies were synthesized to evaluate the effectiveness of DES interventions. Findings indicate that DES models, particularly when applied through scenario-based simulations, consistently demonstrate significant reductions in ED LOS. These outcomes suggest that DES is a valuable decision-support tool for optimizing resource allocation and patient flow. However, implementation requires careful consideration of institutional needs and further validation through real-world trials. Future research should focus on context-specific applications and long-term impact assessment to support sustainable improvements in emergency care.